Perspectives on ethical leadership - Nadisic, Thierry; Patient, David L; Grover, Steven L (Routledge, 2014)
Ethical leadership has come to the forefront of management thought in the twenty-first century in the wake of breaches of judgement and integrity that have plagued international markets. This volume assembles an international cadre of management scholars to explore questions surrounding ethical leadership. Using a variety of methods and approaches, this collection of studies examines how people determine the ethicality of their leaders, the complex connection of trust and those perceptions, and how that affects positive employee outcomes in the private and public sectors. Issues are explored both from the standpoint of behaving unethically and behaving ethically at the individual and firm levels. The diversity of approaches and penetrating insight makes this a valuable resource for anyone interested in understanding the dynamics of ethics and leadership